The Trends in Need Analysis of ESP for Engineering Students: Systematic Literature Review - Musrina; Andi Musdalifah; Irham Bangsawan; Andi Juni Astika (Didaktika: Jurnal Kependidikan, 2024)
This comprehensive review examines 26 articles spanning 2018 to 2023, concentrating on need analysis in English for Specific Purposes (ESP) within the engineering field. The study explores trends in research distribution, geographical and thematic focuses, subject areas within engineering, methodological dimensions, participant demographics, and language skills emphasis. During the study's analytical phase, quantitative data analysis procedures were implemented. Primarily, descriptive statistics such as frequency and percentage were utilized. The data reveals fluctuations in ESP-based research over the specified years, with a notable emphasis on the Engineering department. Most articles originate from countries with an English as a Foreign Language (EFL) context, particularly Indonesia, indicating a strong focus on the need for engineering material in ESP in these regions. The distribution across engineering disciplines highlights the field's multidisciplinary nature, while participant preferences lean towards university settings for research. Speaking skills emerge as the most emphasized, with significant implications for curriculum development. Identified deficiencies in language skills suggest a need for targeted interventions, and recommendations for future research encompass comparative studies across diverse language policies, exploration of workplace needs, balanced language skills emphasis, and the incorporation of authentic content in ESP teaching materials. Overall, the findings provide valuable insights into the evolving landscape of ESP research in engineering and offer directions for further exploration and improvements in educational practices.